Periodontal ligament injection versus routine local infiltration for nonsurgical single posterior maxillary permanent tooth extraction: comparative double-blinded randomized clinical study - Al-Shayyab MH (Dove Medical Press, 2017)
Mohammad H Al-Shayyab Department of Oral and Maxillofacial Surgery, Oral Medicine and Periodontology, School of Dentistry, University of Jordan, Amman, Jordan Aim: The aim of this study was to evaluate the efficacy of, and patients’ subjective responses to, periodontal ligament (PDL) anesthetic injection compared to traditional local-anesthetic infiltration injection for the nonsurgical extraction of one posterior maxillary permanent tooth. Materials and methods: All patients scheduled for nonsurgical symmetrical maxillary posterior permanent tooth extraction in the Department of Oral and Maxillofacial Surgery at the University of Jordan Hospital, Amman, Jordan over a 7-month period were invited to participate in this prospective randomized double-blinded split-mouth study. Every patient received the recommended volume of 2% lidocaine with 1:100,000 epinephrine for PDL injection on the experimental side and for local infiltration on the control side. A visual analog scale (VAS) and verbal rating scale (VRS) were used to describe pain felt during injection and extraction, respectively. Statistical significance was based on probability values <0.05 and measured using Χ2 and Student t-tests and nonparametric Mann–Whitney and Kruskal–Wallis tests. Results: Of the 73 patients eligible for this study, 55 met the inclusion criteria: 32 males and 23 females, with a mean age of 34.87±14.93 years. Differences in VAS scores and VRS data between the two techniques were statistically significant (P<0.001) and in favor of the infiltration injection. Conclusion: The PDL injection may not be the alternative anesthetic technique of choice to routine local infiltration for the nonsurgical extraction of one posterior maxillary permanent tooth. Keywords: PDL injection, infiltration, anesthesia, extraction